Domestic Violence in Senegal: A Quantitative and Qualitative Study - Leye, Mamadou Makhtar Mbacké (Challenges in Disease and Health Research Vol. 5, 2021)
Introduction: Faced with the predominance of domestic violence, the under-denunciation remains shrill among victims linked to socio-cultural constraints. The objective of this study is to make a descriptive analysis of the epidemiological and clinical aspects of domestic violence and the perceptions of victims in Senegal. Methodology: A mixed method was conducted. The data was collected from the court records of female victims of physical and/or sexual violence registered from 2006 to 2015. Female victims of physical and/or sexual violence at the hands of their husbands who had a court record at one of Senegal’s high courts during this period were also included. All records that met the inclusion criteria were selected for the study and the data was analyzed using Epi Info 3.3.2. A qualitative analytical study was carried out. The study population was the victims. Individual interview guides have been produced to collect victims' perceptions of violence. Content analysis supported by thematic analysis was conducted with Iramuteq software. Results: According to the court records of 148 female victims of domestic violence, the average age of the victims was 30.6 ± 10.1 years. More than ¾ (76.4%) of the victims were housekeepers, 82.4% of whom were uneducated. The average age of the perpetrators was 40.4 ± 11.4 years, and they were self-employed in the informal sector in 47.3% of the cases. Additionally, more than ¾ (78.4%) of the perpetrators were uneducated. Eleven women (8% of the victims), were abused while pregnant. Physical violence was predominant (95.3%), while those associated with sexual assault accounted for 4.7% of cases. Of the 7 recorded cases of sexual violence, 3 were cases of unwanted sexual touching, and all cases of physical violence were cases of assault and battery. The violence took place at the home of the perpetrators in 81.8% of cases. In 84.7% of the cases, victims received treatment and care within 24 hours or less. Among the victims, 73% showed clinical lesions. Contusions, hematomas and penetrating wounds were most frequent, representing 23.1%; 19.4% and 13.9% of cases respectively. The husband, the main aggressor, is at the origin of all forms of violence. For example, he beats his wife (physical violence), he insults his wife (verbal abuse) or he refuses his spouse to have sex. Often, for fear of divorce, women conceal the violence suffered from those around them and refuse any denunciation. Conclusion: Despite the low number of cases registered in the judicial system in the past ten years, much more violence is occurring without being denounced by the victims. Therefore, it seems appropriate to increase awareness within the community and break sociocultural barriers that hinder the recognition of women’s rights in the couple.